2016
DOI: 10.1016/j.frl.2015.10.025
|View full text |Cite
|
Sign up to set email alerts
|

Hedging capabilities of bitcoin. Is it the virtual gold?

Abstract: This paper sets out to explore the hedging capabilities of bitcoin by applying the asymmetric GARCH methodology used in investigation of gold. The results show that bitcoin can clearly be used as a hedge against stocks in the Financial Times Stock Exchange Index. Additionally bitcoin can be used as a hedge against the American dollar in the short-term. Bitcoin thereby possess some of the same hedging abilities as gold and can be included in the variety of tools available to market analysts to hedge market spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

38
405
5
26

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 813 publications
(474 citation statements)
references
References 6 publications
38
405
5
26
Order By: Relevance
“…Although the literature on Bitcoin is limited overall, there are still several related studies. Dyhrberg (2016a) investigated the hedging capabilities of Bitcoin by applying the asymmetric GARCH methodology and showed that Bitcoin can clearly be used as a hedge against stocks in the Financial Times Stock Exchange Index and against the American dollar in the shortterm. Dyhrberg (2016b) explored the financial asset capabilities of Bitcoin using GARCH models and showed several similarities to gold and the dollar indicating hedging capabilities and advantages as a medium of exchange.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Although the literature on Bitcoin is limited overall, there are still several related studies. Dyhrberg (2016a) investigated the hedging capabilities of Bitcoin by applying the asymmetric GARCH methodology and showed that Bitcoin can clearly be used as a hedge against stocks in the Financial Times Stock Exchange Index and against the American dollar in the shortterm. Dyhrberg (2016b) explored the financial asset capabilities of Bitcoin using GARCH models and showed several similarities to gold and the dollar indicating hedging capabilities and advantages as a medium of exchange.…”
Section: Literature Reviewmentioning
confidence: 99%
“…They found that Bitcoin prices were influenced by popularity, but also that web content and Bitcoin prices had some predictable power. Dyhrberg (2016a) applied the asymmetric GARCH methodology to explore the hedging capabilities of Bitcoin. It was shown that Bitcoin can be used as a hedge against stocks in the Financial Times Stock Exchange Index and against the American dollar in the short term.…”
Section: Introductionmentioning
confidence: 99%
“…Bouri et al (2016) examine the volatility persistence in the Bitcoin market. However, Dyhrberg (2015a) highlights the hedging ability of Bitcoin against the USD/EUR and USD/GBP exchange rates and UK equities, whereas Dyhrberg (2015b) situates the hedging capability of Bitcoin somewhere _________________________ 1 Dwyer (2015) explained in detail the principles of Bitcoin.…”
Section: Introductionmentioning
confidence: 99%